The effect of cutting parameters and cutting tools on machining performance of carbon graphite material - KAYNAK, YUSUF (TAYLOR & FRANCIS INC, 2020)
The present study focuses on the effects of cutting speed, feed rate and cutting tool material on the machining performance of carbon graphite material. Polycrystalline Diamond (PCD) cutting tools are used in machining experiments and its performance is compared with the tungsten carbide (WC) and Cubic Boron Nitride (CBN) tools. Machining performance criteria such as flank and nose wear and resulting surface topography and roughness of machined parts were studied. This study illustrates that feed rate and cutting tool material play a dominant role in the progressive wear of the cutting tool. The highest feed rate and cutting speed profoundly reduce the tool wear progression. The surface roughness and topography of specimens are remarkably influenced from the tool wear. Major differences are found in the wear mechanisms of PCD and WC and CBN cutting tools.
Keywords: Carbon graphite material; machining performance; tool wear; Polycrystalline Diamond (PCD) tool; Cubic Boron Nitride (CBN) tool; POLYCRYSTALLINE DIAMOND; WEAR; PCD; INSERTS; MICRO